Development of Comic-Based Media for Financial Mathematics Content to Support High School Students’ Mathematical Problem-Solving Skills - Dita Susi Evrihatin; A’yunnisa Tsani; Sunismi Sunismi; Any Herawati; Retno Trisniwati; Dita Susi Evrihatin; A’yunnisa Tsani; Sunismi; Any Herawati; Retno Trisniwati (Universitas Negeri Malang, 2026)
This study aims to develop a mathematics comic as a teaching medium for financial mathematics to support high school students’ mathematical problem-solving skills. This study was motivated by students’ still-low ability to understand the concept of compound interest and solve contextual mathematical problems related to daily life. This study employed the Research and Development (R&D) method using the ADDIE model, which consists of the analysis, design, development, implementation, and evaluation stages. The research subjects included 36 11th-grade high school students, two subject matter experts, two media experts, and one mathematics teacher. The product developed was a context-based mathematical comic that presents the concept of compound interest through visual storytelling, engaging illustrations, and real-life financial scenarios, thereby helping students understand the concept in a more concrete and communicative way. Data collection techniques included observation, interviews, expert validation sheets, a practicality questionnaire, and pretest and posttest instruments. The validation results showed that the developed media met the criteria for high validity, with an average percentage of 81.7%. The results of the teacher practicality test yielded a percentage of 71.9%, and the student response rate was 86%, thus confirming that the media is practical and suitable for use in learning. Based on the pretest and posttest results, it can be concluded that the use of digital comic learning media has a positive impact on students’ problem-solving skills. This is evidenced by an increase in the average score from 56.05 on the pretest to 90.83 on the posttest, accompanied by an increase in the lowest score from 11 to 85 and the highest score from 85 to 100. These results indicate that comic-based learning media can help improve students’ understanding of the material being studied and are suitable for use as learning media in the classroom learning process.